Seismic analysis of two way asymmetric building systems under bi-directional seismic ground motions. - Lin, Jui-Liang (Earthquake engineering & structural dynamics.)
An approximation approch of seismic analysit of two way asymmetric building systems under bi-directional seismic ground motions is proposed. The procedures of uncoupled modal response history analysis (UMRHA) are extended to two-way asymmetric buildings simultaneously excited by two horizontal components of ground motion. Constructing the relationships of two way base shears versus two way roof translations and base torque versus roof rotation in ADRS format for a two way asymmetric building, each modal pushover curve bifurcates into three curves in an inelastic state. A three degree of freedom (3DOF) modal stick is developed to simulate the modal pushover curve with the state bifurcating characteristic. It requires the calculation of the synthetic earthquake and angle B. It is confirmed that the 3DOF modal stick is consistent with single degree of freedom modal stick in an elastic state. A two way asymmetric three story building was analyzed by UMRHA procedure incorporating the proposed 3DOF modal sticks. The analytical results are compared with those obtained from nonlinear response history analysis. It is shown that the 3DOF modal sticks are more rational and effective in dealing with the assessment of two way asymmetric building systems under two directional seismic ground motions.